A social-legal analysis of the challenges to a durable return and reintegration of refugees : the case of Rwanda - Appiagyei-Atua, Kwadwo (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Kwadwo Appiagye-Atua, Faculty of Law, University of Ghana.